MISE EN PLACE Dâ€™UN MODÃˆLE QUALITATIF POUR LA CARTOGRAPHIE DES ZONES Ã€ RISQUE D’Ã‰ROSION HYDRIQUE DANS LA CHAÃŽNE ATLASIQUE: CAS DU BASSIN VERSANT DE LA TESSAOUTE AMONT. (HAUT ATLAS CENTRAL, MAROC) - Elaloui, Abdenbi; Marrakchi, Chakib; Fekri, Ahmed; Maimouni, Soufiane; Aradi, Mohamed (European Scientific Journal, ESJ, 2015)
The catchment areas of the Atlas chain are threatened by water erosion phenomena that can degrade soil quality and cause siltation of potential dams. The objective of this current study is to develop a methodology using remote sensing and geographic information systems (GIS). This serves to map areas at risk of water erosion in the watershed upstream Tessaoute (High Atlas of Morocco). In addition to produce potential erosion risk map that can be used as a tool for land planning. To conduct this study, weâ€™ve chosen to apply on our watershed qualitative model, based on the model proposed by the Bissonnais (2002) and amended by Abaoui et al (2005), as it is applied in the region High Atlas by Bachaoui et al (2007) and Maimouni et al (2012). Through this model the sensitivity of land to erosion is assessed from the sum of the features attributed to classes of three parameters: the land, the friability of materials and the degree of slope. The methodology presented is to integrate in a GIS environment, the three main factors controlling the erosion which enables the establishment of a qualitative model for mapping soil sensitivity to water erosion. The potential erosion risk map derived therefrom shows four areas of vulnerability to water erosion: low, medium, high and very high.